RANCANG BANGUN PROTOTYPE SISTEM E-ARSIP PEMBIAYAAN KPR BERBASIS WEB PADA PT BANK SYARIAH INDONESIA KCP BEKASI TIMUR - -, Satria; Rahayu, Yanti; Agung, Rudi Budi; -, Marisa (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2024)
BSI is one of the banks that still uses a manual KPR financing data archiving system. The problem that occurs at BSI, especially the Bekasi branch, is that requests for financing copies take 14 working days or even longer. Therefore, the information system for archiving KPR financing documents at BSI, which was initially still manual, has become a computerized information system. So, an e-archive for KPR financing was built at PT Bank Syariah Indonesia using the prototype method. Where the existence of the E-archive system makes it easier for the financing department to manage KPR financing archives for Bank Syariah Indonesia customers and also makes it easier to search and store data, especially data related to financing, which can be done easily.